2017
DOI: 10.1002/dta.2299
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine as a chemical scavenger for sulfur mustard: New insights by mass spectrometry

Abstract: The vesicant sulfur mustard (SM) is a banned chemical warfare agent. Although, SM has been used in combat since WWI, there is no causal therapy currently available. Accordingly, development and investigation of antidotes and scavengers targeting SM are of high clinical relevance. N-acetylcysteine (NAC) was shown to mitigate symptoms of SM intoxications in vitro and in vivo. However, it is still unclear whether the beneficial effects of NAC are only due to physiological processes or also due to chemical scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Most recently, SM was used by the terrorist group islamic state of Iraq and the Levant (ISIL) in Syria and Northern Iraq, 3–6 and accidental exposures have also been reported, 7,8 thus underlining the need to understand the pathophysiology, to develop appropriate antidotes, and to establish analytical methods for biomedical verification of poisoning. Once SM enters the bloodstream, it forms adducts with various molecules by alkylation of, for example, proteins, DNA, hormones, glutathione, and N ‐acetylcysteine 9–14 . Human serum albumin (HSA) is a well‐known target of SM being alkylated at diverse amino acid residues including cysteine 34 (Cys 34 ) 3,8,14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, SM was used by the terrorist group islamic state of Iraq and the Levant (ISIL) in Syria and Northern Iraq, 3–6 and accidental exposures have also been reported, 7,8 thus underlining the need to understand the pathophysiology, to develop appropriate antidotes, and to establish analytical methods for biomedical verification of poisoning. Once SM enters the bloodstream, it forms adducts with various molecules by alkylation of, for example, proteins, DNA, hormones, glutathione, and N ‐acetylcysteine 9–14 . Human serum albumin (HSA) is a well‐known target of SM being alkylated at diverse amino acid residues including cysteine 34 (Cys 34 ) 3,8,14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…This peptide also derived from pepsin-mediated cleavage and contains the Cys 34 -residue. It could be excluded, that the increasing amounts of LQQC(-HETE)PFED were produced by the reaction with remaining SM as under reaction conditions applied, SM should have been hydrolyzed completely within the first 30 minutes (period of half-change in PBS: 3.9 minutes) 25. More likely, the additional alkylation of Cys 34 was due to the nucleophilic attack of the free thiol-group to the Cα next to the sulfonium sulfur atom of the HETE moiety of the alkylated Met 329 .The regeneration of Met by the nucleophilic attack of a thiol group is Long-term stability of alkylated Met 329 in human serum.…”
mentioning
confidence: 99%
“…No correlations were made with cellular viability in these studies, although it was concluded that chemical scavenging of H by NAC was not the major route through which these effects occurred [ 71 ], a conclusion later supported by mass spectrometric studies where NAC and H were co-incubated in either phosphate buffered saline or human serum. In this work, although reaction products of NAC and H were detected and identified, “analyses clearly documented minor reactivity not significantly contributing to reduction of SM concentrations” [ 72 ].…”
Section: Nac and Sulphur Mustardmentioning
confidence: 99%